The Construction of Moral Values in Surah Al-Baqarah Verse 83 Tafsir As-Sa'di and Implementation at Islamic Boarding School - Muh. Sakir; Muhammad Yusuf; Agussalim Agussalim (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
This study aims to analyze the construction of moral values in Surah al-Baqarah verse 83 based on Tafsir As-Sa'di and examine its implementation in fostering students at the Annail Islamic Boarding School, Gowa Regency. The research uses a qualitative approach with a descriptive-analytical type through a combination of literature research and field research. Data collection techniques were carried out through documentation studies, in-depth interviews, and participatory observations, while data analysis used content analysis, thematic analysis, and descriptive-contextual. The results of the study show that Surah al-Baqarah verse 83 contains an integrative moral construction, including monotheism as a moral foundation, the obligation to serve parents and relatives, social concern for orphans and the poor, universal communication ethics, and the integration of ritual and social worship. The implementation of these values at the Annail Islamic Boarding School is carried out through the habituation of worship, adab education, strengthening ukhuwah, and the enforcement of discipline, which has been proven to form religious character, social concern, and personal responsibility of students. This study confirms that the contextual internalization of Qur'anic moral values can be an effective model for fostering the character of students in facing the moral challenges of contemporary society.